2012
DOI: 10.1186/1471-2407-12-583
|View full text |Cite
|
Sign up to set email alerts
|

The role of MMP-1 in breast cancer growth and metastasis to the brain in a xenograft model

Abstract: BackgroundBrain metastasis is an increasingly common complication for breast cancer patients; approximately 15– 30% of breast cancer patients develop brain metastasis. However, relatively little is known about how these metastases form, and what phenotypes are characteristic of cells with brain metastasizing potential. In this study, we show that the targeted knockdown of MMP-1 in breast cancer cells with enhanced brain metastatic ability not only reduced primary tumor growth, but also significantly inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
110
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 49 publications
8
110
0
1
Order By: Relevance
“…In this report we have shown that MMP1 indeed promotes brain metastasis by increasing the permeability of gap junction of BBB through degradation of Claudin and Occludin. Our result is consistent with the previous observation by Liu et al (47), who showed that knockdown of MMP1 blocked primary growth and distant metastasis of breast Endothelial cells…”
Section: Discussionsupporting
confidence: 83%
“…In this report we have shown that MMP1 indeed promotes brain metastasis by increasing the permeability of gap junction of BBB through degradation of Claudin and Occludin. Our result is consistent with the previous observation by Liu et al (47), who showed that knockdown of MMP1 blocked primary growth and distant metastasis of breast Endothelial cells…”
Section: Discussionsupporting
confidence: 83%
“…It has been reported that MMP1 and MMP13 are involved in breast cancer metastasis (24,25). Thus, our data indicate that NF-kB signaling contributes to cell invasiveness at least in part through MMP1 and MMP13 in HER2-positive breast cancer cells.…”
Section: Discussionmentioning
confidence: 52%
“…However, it is not clear if MMP-1 activity toward collagen type I is important for osteoblasts. While MMP-1 is not generally found to be expressed by osteoclasts, there is evidence that it may be involved in bone resorption in pathological conditions [113,116,117].…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…MMP-1, also known as interstitial collagenase or fibroblast collagenase, is involved in the breakdown of extracellular matrix in normal physiological processes, such as embryonic development, reproduction, and tissue remodeling, as well as in disease processes, such as arthritis and cancer metastasis [106,112,113]. Osteoblasts have been demonstrated to produce MMP-1, which may affect their differentiation [114].…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%